Democracy in Progress in Contemporary Brazil: Corruption, Organized Crime, Violence and New Paths to the Rule of Law - Adorno, Sergio (International Journal of Criminology and Sociology, 2013)
Although the transition to democracy began in the middle of 1980’s, Brazilian society has not yet experienced a peaceful social life. New forms of violence have emerged in in the last two decades including the increase of violent crimes, gross human rights violations, organized crime and conflicts within social and subjective relationships. The paper discusses the policies of the Fernando Henrique Cardoso administrations (1995-2002) regarding human rights and public security. It examines the social and political constraints in which government initiatives are based and the successes as well as the failures on the efficiency of these public policies.